2018
DOI: 10.7150/jca.26264
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 Polymorphism and bladder cancer risk: a meta-analysis and emphasis on the role of tumor or smoking status

Abstract: Background: Various studies had explored the relationship between TP53 codon 72 polymorphisms and the risk of bladder cancer (BC). However, their results remained inconsistent and the definite role of smoking or tumor status associated with this polymorphism in BC cases was seldom involved. Hence, this meta-analysis was to disclose such associations.Methods: Systematical and comprehensive retrieval of online databases PubMed, PMC, EMBASE and Web of Science were conducted to obtain eligible studies, up to May 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…It was estimated that there were 430,000 new cases and 165,000 bladder cancer deaths in 2012 (2). Risk factors such as genetic factors (3,4), secondhand smoking (5), diabetes mellitus (6), vitamin A (7), fruits and vegetables (8) and so on had been well documented. Previous paper had been suggested that dietary may be an important factors in the development of bladder cancer because many dietrelated metabolites were in direct contacting with the bladder epithelium during excretion (9).…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that there were 430,000 new cases and 165,000 bladder cancer deaths in 2012 (2). Risk factors such as genetic factors (3,4), secondhand smoking (5), diabetes mellitus (6), vitamin A (7), fruits and vegetables (8) and so on had been well documented. Previous paper had been suggested that dietary may be an important factors in the development of bladder cancer because many dietrelated metabolites were in direct contacting with the bladder epithelium during excretion (9).…”
Section: Introductionmentioning
confidence: 99%
“…According to our findings, the association of the MTHFR rs1801133 (677C>T) and rs180113 (1298A>C) polymorphisms with bladder cancer may be due to differences in ethnicity, genetic background, life style, smoking habits, and etc. in a meta-analysis, Zhang et al, (2018) verified the relationship between TP53 codon 72 and bladder cancer risk in Asians, but not Caucasians. These results indicated that genetic variants might be an ethnicity related factor of susceptibility to bladder cancer.…”
Section: Discussionmentioning
confidence: 88%
“…Polymorphisms in PAI-1 and TP53 genes may be involved in their expression and thus contribute to breast cancer susceptibility, progression, and therapeutic responses [22, 34]. Various studies have suggested the association of these polymorphisms in the development of various cancers including endometrium, colorectal, lung, and breast cancers [14, 22, 35]. In this current paper, we investigated the effects of 2 polymorphisms of codon 72 in TP53 and 4G/5G of PAI-1 in Iranian-Azeri women with the risk of breast cancer.…”
Section: Discussion/conclusionmentioning
confidence: 99%